Asymptotic analysis of quenching problems - Fila, Marek; Kawohl, Bernhard (The Rocky Mountain journal of mathematics, 1992)
Rocky Mountain Journal of Mathematics
First available in Project Euclid: 5. Juni 2007
Gesehen am 29.06.2023